INSECTICIDE RESISTANCE STATUS OF ANOPHELES GAMBIAE BREEDING IN STAGNANT WATER BODIES IN LAGOS, NIGERIA. - J. B. Olojede; W. Oyibo A.O. Oduola I.O. Oyewole, T.S.Awolola (UNILAG Journal of Medicine, Science and Technology, 2019)
Anopheles gambiae, the major Afro-tropical malaria vector is resistant to pyrethroid insecticide and this is threatening the impact of malaria control efforts using insecticides. In this study, the major malaria vector species from stagnant water bodies and their susceptibility status to pyrethroid insecticide was determined in some areas of Lagos state, Nigeria. Anopheles larvae were sampled from three areas of Lagos, namely Akoka, Idiaraba and Okobaba and raised to adulthood in the insectary. Two to three days old adult female mosquitoes were exposed to 0.75% permethrin and 0.05% lambdacyhalothrin using the World Health Organization (WHO) insecticide susceptibility test kits. All samples exposed were identified morphologically and by Polymerase chain reaction (peR) using the Anopheles gambiae species specific peR assay. All mosquito samples tested belong to the A. gambiae complex. The peR assay sho-wed a mixture of A. gambiae and A. arabiensis: (32%: 68%) at Akoka, (51%: 49%) at Idiaraba, and 100%A. arabiensis at Okobaba. The 24 hr post exposu.re mortality rates in permethrin and Iambdacyhalothrin were 60% and 100% at Akoka, 49% and 60% at Idiaraba, 69% GIld 71 % at Okobaba respectively. The Knock down time, KDT50 and KDT95 (Time takenfor 50% and 95% of the test population to be knocked down) for the entire sample tested was between 23-31 minutes and> 1 hr respectively. This result showed that the A. gambiae s.l used were more resistant to permethrin than to lambdacyhalothrin. Although Anopheles resistance to perm eth rin . has been reported in other sites in Lagos, this is the first report on resistance of Anopheles gambiae s.s to lambdacyhalothrin in Nigeria. This study also provides early evidence that A. gambiae is adapting to stagnant water. The level of insecticide resistance is a concern and could be of interest in the epidemiology of urban malaria and hopefully a target for larviciding.